Mobile-Assisted Language Learning (MALL) in English language acquisition: a critical literature review - Kristianus Erwin Gael; Dewi Satria Elmiana (Journal of English Language Teaching Innovations and Materials (Jeltim), 2021)
The objective of this study is  ‘how effective mobile apps in learning English?’ by exploring the use of mobile apps in English as a Second Language (ESL)/English as a Foreign Language (EFL) acquisition. It examines how employing MALL in learning English can improve students’ receptive skills, productive skills, and other skills by conducting critical literature review to answer the research question. The results showed that employing mobile applications in learning English is effective to develop L2 learners’ English skills and also Mobile apps help L2 learners in learning English both as the second and foreign language. Interestingly, in the situation of the global pandemic which many schools are closed, mobile technology has helped students in learning English skills. It can be suggested that by employing Mobile Assisted Language Learning (MALL) in learning English skills plays a crucial role in the situation of the global pandemic of COVID 19 where teachers and students can use mobile apps both in and outside the classroom because it is convenient and user friendly.